Analysis of climate and population dynamics of Conomoporpha cramerella pest in North Luwu. Issue 1 (April 2020) - Zul, F; Kaimuddin,; Rafiuddin,
Abstract: Indonesia is one of the most widely grown cocoa growing countries in the world and is the third largest cocoa producing country after Ivory Coast and Ghana. Cocoa is a plant that is not native to Indonesia but is able to adapt and grow well in Indonesia. Geographic Information System (GIS) is a system created to facilitate mapping by using structured data by setting spatial or geographical coordinates in utilizing and planning land use. Decrease in yields on cocoa is partly due to Cocoa Fruit Borer (CPB) ( Conomoporpha cramerella Snellen). There is a very close relationship between local climatic conditions and the dynamics of pest populations, especially the factors of temperature, humidity, and altitude. The lowest percentage for mild attacks of CPB pests over the past 5 years ignoring missing data is in April 2014, 2015 and 2016 was 15.30%. Whereas the highest percentage of severe CPB pests in the last five years was in February 2015 which was 88.09%. Controlling the CPB pests can be done by using CPB pest resistant clones as well as improving plant maintenance management.